2004
DOI: 10.1111/1469-8986.2004.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic processing with aging: An event‐related potential study

Abstract: To assess age-related changes in simple syntactic processing with normal aging, event-related brain potentials (ERPs) elicited by grammatical number violations as individuals read sentences for comprehension were analyzed. Violations were found to elicit a P600 of equal amplitude and latency regardless of an individual's age. Instead, advancing age was associated with a change in the scalp distribution of the P600 effect, being less asymmetric and more frontal (though still with a parietal maximum) in older th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
35
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 109 publications
(156 reference statements)
11
35
1
5
Order By: Relevance
“…The overall morphology of the brain responses from younger and older adults is similar: both groups show early sensory responses followed by a wide-spread negativity (N400). However, consistent with prior observations of ERP responses from healthy older adults (e.g., Federmeier & Kutas, 2005; Federmeier, McLennan, De Ochoa, & Kutas, 2002; Kemmer, Coulson, De Ochoa, & Kutas, 2004; Kutas & Iragui, 1998), N1 responses (around 160 ms over posterior sites and 110 ms over frontal sites) appear to be enhanced while P2 responses (around 200–250 ms over posterior sites and 150–200 ms over frontal sites) are notably reduced in the older sample; in addition, the amplitude of the N400 is smaller for older adults.…”
Section: Resultssupporting
confidence: 91%
“…The overall morphology of the brain responses from younger and older adults is similar: both groups show early sensory responses followed by a wide-spread negativity (N400). However, consistent with prior observations of ERP responses from healthy older adults (e.g., Federmeier & Kutas, 2005; Federmeier, McLennan, De Ochoa, & Kutas, 2002; Kemmer, Coulson, De Ochoa, & Kutas, 2004; Kutas & Iragui, 1998), N1 responses (around 160 ms over posterior sites and 110 ms over frontal sites) appear to be enhanced while P2 responses (around 200–250 ms over posterior sites and 150–200 ms over frontal sites) are notably reduced in the older sample; in addition, the amplitude of the N400 is smaller for older adults.…”
Section: Resultssupporting
confidence: 91%
“…A difference in the LPC amplitude between younger and older adults was reported by Federmeirer et al (2003) in their study involving lexically associated and unassociated word pairs embedded in natural speech. In contrast, Kemmer et al (2004) found no significant differences between age groups for the amplitude or latency of the LPC as elicited by grammatical number violations in visually presented sentences. These findings were observed in spite of lower accuracy and slower response times for their older participants.…”
Section: Sumariocontrasting
confidence: 72%
“…Kemmer et al (2004) found that relative to syntactically well-formed control sentences, both sorts of grammatical number violations elicited a sustained centro-parietal positivity evident between 500 and 800 ms after word onset (P600). These data were in keeping with reports across a number of different languages that grammatical number violations, be they subject/verb or reflexive pronoun/antecedent grammatical number agreement or other violations, elicit a P600 component (English: Coulson et al, 1998; Osterhout et al, 1996; Osterhout and Mobley, 1995; Dutch: Hagoort and Brown, 2000; Hagoort et al, 1993; Vos et al, 2001; German: Münte et al, 1997).…”
Section: Introductionmentioning
confidence: 95%
“…The linguistic materials used in the present study were the same as those used in an ERP study reported by Kemmer et al (2004) in which all materials were presented centrally. Kemmer et al (2004) found that relative to syntactically well-formed control sentences, both sorts of grammatical number violations elicited a sustained centro-parietal positivity evident between 500 and 800 ms after word onset (P600).…”
Section: Introductionmentioning
confidence: 99%